1987
DOI: 10.1002/ajim.4700110607
|View full text |Cite
|
Sign up to set email alerts
|

Increased chromium and nickel content in lung tissue and bronchial carcinoma

Abstract: In 25 random autopsies, chromium (Cr) and nickel (Ni) in lung tissue and regional lymph nodes were analysed by means of flameless atomic absorption spectrometry (AAS). The subjects originate from Bochum in the Ruhr District, which is defined as a particular pollution area with locally high Cr and Ni emissions. The subjects examined from Bochum (BO) and vicinity have Cr and Ni concentrations about 5 and 6 times higher than those in a previous series form Münster (MS) and vicinity (outside the particular polluti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
17
0
2

Year Published

1989
1989
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(19 citation statements)
references
References 11 publications
0
17
0
2
Order By: Relevance
“…However, considering the relatively small number oftest subjects and the considerable interindividual variation, evidence at present is not sufficient to reach a conclusion that the nickel detected in the lung tissue is a major contributory cause of the development of occupational lung cancer (31). Therefore, investigations using larger numbers of subjects are necessary to understand this relationship.…”
Section: Accumulation Of Nickel In Human Lungsmentioning
confidence: 98%
“…However, considering the relatively small number oftest subjects and the considerable interindividual variation, evidence at present is not sufficient to reach a conclusion that the nickel detected in the lung tissue is a major contributory cause of the development of occupational lung cancer (31). Therefore, investigations using larger numbers of subjects are necessary to understand this relationship.…”
Section: Accumulation Of Nickel In Human Lungsmentioning
confidence: 98%
“…Determining of total concentrations of the TE in serum and tissues is unlikely to be a sufficiently sensitive or specific marker. What might bring about a change in our knowledge is the speciation of the various forms of trace element found in the organism in relation to lung cancer [4][5][6][8][9][10].…”
Section: Introductionmentioning
confidence: 99%
“…The role of trace elements in the development or inhibition of cancer is still unclear, and numerous investigations have been carried out on this subject [4,5,[8][9][10][11][12][13][14][15][16][17][18][19]. Many of these studies have focused on heavy elements inducing carcinogenity.…”
Section: Introductionmentioning
confidence: 99%
“…Serum Cu levels were found to be lower in lung cancer patients than in healthy people [2]. Levels of Ni were found to be increased in 15 patients with breast cancer [3].…”
Section: Introductionmentioning
confidence: 99%
“…In a study on colorectal cancer patients, varying levels of Fe, Cu, Mn and S were found [1][2][3][4]. Levels of Na, Mg, Ca, Se, Rb and Mo were observed to decrease in the plasma of lung cancer patients undergoing radiotherapy.…”
Section: Introductionmentioning
confidence: 99%